A New Perspective on the Apparent Solubility of Dissolved Black Carbon - Wagner, Sasha; Ding, Yan; Jaffé, Rudolf (Frontiers in Earth Science, 2017)
Black carbon (BC), pyrogenic organic matter generated from the incomplete combustion of biomass, is ubiquitous in the environment. The molecular structures which comprise the BC pool of compounds are defined by their condensed aromatic core structures polysubstituted with O-containing functionalities (e.g., carboxyl groups). Despite the apparent hydrophobicity of BC molecules, a considerable portion of BC is translocated from terrestrial to aquatic systems in the form of dissolved BC (DBC). However, the specific biogeochemical mechanisms which control the transfer of BC from the land to the water remain elusive. In the current study, the apparent solubility of DBC was inferred from octanol-water partition coefficients (Kow) modeled for proposed DBC structures with varying degrees of polycondensation and polar functionality. Modeled Kow values indicated that DBC molecules with small aromatic ring systems and high degrees of hydrophilic functionality may be truly solubilized in the aqueous phase. However, large and highly condensed DBC structures yielded high Kow values, which suggested that a considerable portion of the DBC pool which has been quantified in aquatic environments is not truly dissolved. We hypothesized that other DOM components may act as mediators in the solubilization of condensed aromatic molecules and serve to increase the solubility of DBC via hydrophobic, intermolecular associations. This hypothesis was tested through controlled leaching experiments to determine whether the mobilization of DBC from particulate soils and chars became enhanced in the presence of DOM. However, we observed that characteristics inherent to each sample type had a greater influence than added DOM on the apparent solubility of DBC. In addition, the direct comparison of molecular marker (benzenepolycarboxylic acids) and ultrahigh resolution mass spectral data (FT-ICR/MS) on leachates obtained from the same set of soils and char did not show a clear overlap in DBC quantification or characterization between the two analytical methods. Correlations between FT-ICR/MS results and BPCA were not significant possibly due to differences in the methodological windows and/or small sample size. Our results were unable to provide evidence in support of proposed hydrophobic interactions between DOM and DBC, suggesting that other physical/chemical mechanisms play important roles in the dissolution of BC.